Profiles of patients with urinary incontinence in the Department of Child Health, Cipto Mangunkusumo Hospital - Eveline P N; Taralan Tambunan; Sri Rezeki S Hadinegoro (Indonesian Pediatric Society Publishing House, 2016)
Background Urinary incontinence (UI) in children is a form of wetting. Early diagnosis and treatment are mandatory to avoid complications such as recurrent urinary tract infections (UTI), vesicoureteral reflux (VUR), or renal damage. Objective To study the profiles and clinical course of UI in chil- dren treated in Cipto Mangunkusumo Hospital. Methods The study was divided into 2 parts. The first part was a review of patients with UI at Cipto Mangunkusumo Hospital from January 2000 to December 2003. The second was a case series of patients followed up for at least 6 months. Results There were 35 UI patients aged 3 months to 16 years, mostly between 1 to 5 years old, 16 were males and 19 females. The most prevalent etiology was myelodysplasia (15 cases) fol- lowed by posterior urethral valve, and bladder tumor. The most prominent clinical presentation of neurophatic bladder-sphincter dysfunction was wetting, while those of patients with structural in- continence and non-neuropathic bladder-sphincter dysfunction were fever and polakysuria. Most patients had been suffering from renal insufficiency since their first visit. Clean intermittent catheter- ization (CIC) was the treatment of choice. In a six-month follow-up of 14 patients who received adequate treatment, renal function could be maintained at relatively stable condition in most cases. Conclusions Myelodysplasia was the most common etiology of UI. Most patients had renal insufficiency or renal failure since their first visit, reflecting a extended period of relapse before patients seek medical help. Renal function can be maintained by adequate treatment in most cases